Assessing the variables of personal characteristics affecting the formation of investment intentionality: case of unit trust / Tan Kwe Lu ... [et al.] - Lu, Tan Kwe; Abdullah, Azlina; Abdul Latif, Nurul Wahilah; Wei Kiong, Irene Ting (2012)
The paper examines the personal characteristics on unit trust investment among working adults in Malaysia. Specifically the objective of the study to investigate empirically the extent to which the personal traits contribute to the intention to invest in unit trust. Structured questionnaires were deployed to various strategic locations in Malaysia randomly and conveniently selected. The personal characteristics were classified into work ethic, pursuit of excellence, mastery, dominance, internal attributing factor, chance attributing factor and powerful others. The coefficient of determination R2 shows that 13.8% of the variance of intention to invest is explained by the variance of work ethics, excellence, mastery, dominance, chance attributing, internal attributing and powerful others.